INCREASING THE LEVEL OF CITIZENS’ LEGAL CULTURE BY INTRODUCING INNOVATIVE DIGITAL TECHNOLOGIES IN RUSSIA - Barakina, Elena; Bagreeva, Elena; Chvorovich, Dragana (Revista Inclusiones, 2020)
Law-making activity at federal and regional levels actualizes implementation of rapidly developing technologies, creating the optimal regime for its users. The authors analyze provision and content of the information portals, which show the condition of law-making activity at federal and regional levels. It is proved that the distributed registry system is an indispensable technology. The authors identify the principles of promoting the citizens’ legal culture and assert that implementation of these principles, together with using the distributed registry system, will facilitate information exchange between the users of the aforementioned platform.